The Structure of Quaternary Iron-Based Alloy Obtained at High and Ultrahigh Cooling Rates - Kovalevskaya Zh. G. Zhanna Gennadievna (Materials and Technologies in Powder Metallurgy and Additive Manufacturing, 2016)
Title screen